1997
DOI: 10.1051/rnd:19970101
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in CGRP and CT levels either contained in or released by CA-77 C cells after combined treatments with 1,25-dihydroxyvitamin D 3 analogues and 9-cis retinoic acid

Abstract: Summary ― This study examined the action of 9-cis retinoic acid and 1,25-dihydroxyvitamin D 3 analogues (KH 1060, EB 1089 and MC 903) on the release of calcitonin (CT) and calcitonin gene-related peptide (CGRP) in the rat C cell line CA-77. This cell line mainly secretes CGRP. Using radioimmunoassays (RIA S ) for CT and CGRP, we measured the release of both peptides in the culture medium as well as the amount of these proteins contained in the CA-77 C cells. 9-cis retinoic acid decreased the release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In addition to conveying signals in an afferent manner away from peripheral tissues (pain, temperature, proprioception, noxious chemical signals), some peripheral neurons act in an efferent fashion to secrete CGRP, which can impinge upon inflammation and hemodynamics (see [60, 61]). CGRP expression by spinal cord neurons is up-regulated by dietary Ca in the rat [62] and expression is reduced by calcitriol treatment of C-cells or thyroid cells in culture [6365]. This calcium- and inflammation-regulated peptide appears to have important immunomodulatory actions by 1) tempering inflammation through NFkB inhibition and 2) increasing endothelial production of PGI 2 , a prostaglandin with anti-inflammatory activities [61].…”
Section: Dairy and Cardiometabolic Health: Potential Mechanismsmentioning
confidence: 99%
“…In addition to conveying signals in an afferent manner away from peripheral tissues (pain, temperature, proprioception, noxious chemical signals), some peripheral neurons act in an efferent fashion to secrete CGRP, which can impinge upon inflammation and hemodynamics (see [60, 61]). CGRP expression by spinal cord neurons is up-regulated by dietary Ca in the rat [62] and expression is reduced by calcitriol treatment of C-cells or thyroid cells in culture [6365]. This calcium- and inflammation-regulated peptide appears to have important immunomodulatory actions by 1) tempering inflammation through NFkB inhibition and 2) increasing endothelial production of PGI 2 , a prostaglandin with anti-inflammatory activities [61].…”
Section: Dairy and Cardiometabolic Health: Potential Mechanismsmentioning
confidence: 99%
“…The effect of retinol on thyroid C cells is still unknown (4). An in vitro study on the rat C cell line CA-77 showed a decrease in calcitonin release due to retinoid acid 9-cis (55), while all-trans retinoic acid did not seem to have an effect on a human medullary thyroid carcinoma cell line (56). Furthermore, no data suggest the physiological presence of retinoids in thyroid parafollicular cells (3).…”
Section: Vitamin a And Thyroid Cancermentioning
confidence: 99%
“…No information has been reported about a role of RA and calcitonin secretion by normal thyroid C cells. In vitro , 9-cis RA decreases the release of calcitonin in the rat C cell line CA-77 ( 57 ), but no data are available about the spontaneous presence of 9-cis RA in C cells. atRA had no significant effect on a human medullary thyroid carcinoma cell line ( 58 ).…”
Section: Vitamin a And The Hypothalamo–pituitary–peripheral Gland Axementioning
confidence: 99%